Fresno Chapter of Women's International League for Peace and Freedom Celebrating Louise Erickson and Marcia McLane - Watkins, Howard::::::::: (1989)
Back of heads; Howard Watkins with Marcia McLane w/ granddaughter and Louise Erickson